Responding to FASD: what social and community service professionals do in the absence of diagnostic services and practice standards. Issue 1 (18th February 2019) - Bagley, Kerryn
Abstract : Purpose: The purpose of this paper is to ascertain the experiences and practices of social and community service professionals working with Fetal Alcohol Spectrum Disorder (FASD) or suspected FASD in New Zealand. Design/methodology/approach: The research examined professionals' empirical experience of working with FASD or suspected FASD. In total, 21 participants working in practice settings relevant to dual diagnosis were interviewed, with each interview being of 1–2 h duration. The interview data were transcribed and coded using the constant-comparative method in order to derive themes. Findings: Participants identified a number of barriers to understanding or working with FASD: the limited knowledge of FASD and the absence of FASD from training contexts, difficulty obtaining institutional support and the challenge of working without a diagnosis. Participants also articulated a range of strategies for approaching FASD within the identified barriers of their practice contexts, specifically: working with alternative diagnoses, focussing on adjusting expectations, adopting a strengths-based approach, actively advocating for clients when working with other sectors and systems and focussing on prevention education. Originality/value: This research expands the knowledge base for social and community service practice in contexts where FASD maybe a factor contributing to poor health and well-being outcomes for clients. It clarifies the challenges that professionals face when encountering FASD or suspected FASD in their work, reveals key gaps in individual and systemic knowledge about FASD and provides new insight into what professionals do to address these challenges. It also adds to the body of research concerning FASD in the Australasian context more broadly.